MPR to Support The Sales of ICT Education - Neonisa, Didier (Humaniora, 2010)
In the era of globalization the development of economy in each country is determined on how they develop and utilize Information and Communication Technology (ICT) in their business activity. However, Marketing Public Relations (MPR) is also the most appropriate strategy for Education institute, because in nature education institute has to create long term relationship with their student. Therefore MPR should at least encompass three disciplines of studies and professions, in which are strategic management, marketing and public relations. For BINUS Center, awareness can be gain through referral activity. Advocacy or referral have dominant effect in building trust (believe), other than that publication also play a role in creating a trustworthy image towards BINUS Center. Marketing Public Relation is an effective marketing strategy for ICT education. Based on the quantitative research the majority of BINUS Center target market is in the age bracket 18-22 years old. In correlation with that fact the qualitative research has shown that MPR is effective in supporting the enrollment decision towards BINUS Center.